2001
DOI: 10.2337/diabetes.50.7.1627
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Effects on Skin Keratinocytes

Abstract: Altered skin wound healing is a common cause of morbidity and mortality among diabetic patients. However, the molecular mechanisms whereby diabetes alters skin physiology have not been elucidated. In this study, we investigated the relative roles of hyperglycemia, insulin, and IGF-I, all of which are abnormal in diabetes, in primary murine skin keratinocytes. These cells proliferate and differentiate in vitro in a manner similar to skin in vivo. It was found that in the presence of high glucose (20 mmol/l), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
0
11

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(146 citation statements)
references
References 51 publications
10
122
0
11
Order By: Relevance
“…Lack of InsR in keratinocytes led to an abrogation of glucose uptake and an impairment of differentiation. 17,18 Additionally, these findings clearly impact nonwounded diabetic skin that was characterized by a markedly reduced expression of InsR.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Lack of InsR in keratinocytes led to an abrogation of glucose uptake and an impairment of differentiation. 17,18 Additionally, these findings clearly impact nonwounded diabetic skin that was characterized by a markedly reduced expression of InsR.…”
Section: Discussionmentioning
confidence: 92%
“…In line, skin keratinocytes have been shown to express the insulin receptor (InsR), which is functionally implicated in keratinocyte differentiation and glucose uptake. 17,18 There is increasing evidence for a functional link between insulin resistance, obesity, and diabetes. Initial studies demonstrated an increase in adipocyte-derived tumor necrosis factor (TNF)-␣ in obese rodents that was functionally connected to insulin resistance.…”
mentioning
confidence: 99%
“…Keratynocyty na powierzchni mają m.in. transporter glukozy GLUT1, którego ekspresja obniża się w odpowiedzi na hiperglikemię [9]. Powoduje to powstanie swoistego błędnego koła -mniej glukozy przechodzi do keratynocytów, wzrasta natomiast jej stężenie pozakomórkowe i obniża się ekspresja GLUT1.…”
Section: Wprowadzenieunclassified
“…Powoduje to powstanie swoistego błędnego koła -mniej glukozy przechodzi do keratynocytów, wzrasta natomiast jej stężenie pozakomórkowe i obniża się ekspresja GLUT1. Podobna zależność została opisana także dla komórek łożyska, mięśni gładkich i szkieletowych oraz endotelium [9][10][11][12]. W kilku badaniach stwierdzono, że insulina i insulinopodobny czynnik wzrostu 1 (ang.…”
Section: Wprowadzenieunclassified
“…Moreover, the exposure of keratinocytes to high glucose conditions could lead to an inhibition of the proliferation and autophosphorylation of insulin-like growth factor. Therefore, the skin cells proliferation-differentiation balance could be altered by high glucose (Spravchikov et al, 2001), which might affect the functions of the SC (Seirafi et al, 2008). Besides, microcirculation and dysmetabolism are also involved in the diabetic skin damage.…”
Section: Introductionmentioning
confidence: 99%